1968
DOI: 10.1113/jphysiol.1968.sp008655
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of kallikrein and its role in vasodilatation in the submaxillary gland

Abstract: SUM1MARY1. The effects of parasympathetic (chorda) and sympathetic nerve stimulation on the concentration and output of kallikrein secreted in saliva from the cat's submaxillary gland were compared. Sympathetic stimulation always produced a much higher concentration (up to 500 times) and output (up to 390 times) of kallikrein than parasympathetic stimulation. In the dog, in which sympathetic nerve stimulation produces little or no secretion from the submaxillary gland, there was also a marked increase in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
1

Year Published

1970
1970
1989
1989

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 16 publications
4
25
1
1
Order By: Relevance
“…Both groups made use of the fact that parasympathetic nerve stimulation causes marked secretion but relatively little reduction in kallikrein content of the gland, whereas sympathetic nerve stimulation which causes less secretion can practically deplete the gland of its kallikrein (Beilenson, Schachter & Smaje, 1968). Both Barton et al (1975) and Garrett & Kidd (1975) came to the same conclusion, viz.…”
Section: Introductionmentioning
confidence: 53%
“…Both groups made use of the fact that parasympathetic nerve stimulation causes marked secretion but relatively little reduction in kallikrein content of the gland, whereas sympathetic nerve stimulation which causes less secretion can practically deplete the gland of its kallikrein (Beilenson, Schachter & Smaje, 1968). Both Barton et al (1975) and Garrett & Kidd (1975) came to the same conclusion, viz.…”
Section: Introductionmentioning
confidence: 53%
“…Are the substances released together or separately? The experiments of Beilenson et al (48) and Darke and Smaje (49) show that salivation and vasodilation are simultaneously activated by nerve stimulation. This observation has also been made in the nasal mucosa (4), thus indicating a concomitant release of VIP and AcCho.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Beilenson, Schachter & Smaje (1968) on submandibular glands of cats, using bioassay for determining kallikrein activity, showed it was secreted mainly by sympathetic stimulation; nevertheless, small amounts also entered parasympathetic saliva. These authors also showed that with both types of stimulation the kallikrein content of saliva tended to decrease with time.…”
Section: Introductionmentioning
confidence: 99%